Analysis of research groups of psychology of sport and exercise in Brazil Análise dos grupos de pesquisa em psicologia do esporte e do exercício no Brasil - Dominsk F.H.* (2017)
© 2017 Colégio Brasileiro de Ciências do EsporteThe aim of this study was to analyze the geographic distribution and scientific production of research groups of Psychology of Sport and Exercise in Brazil. This is a descriptive and systematic study realized on the current database Directory of Research Groups in Brazil available on the website of the National Council for Scientific and Technological Development. Altogether, 29 research groups were located. Most of research groups are located in São Paulo (20.6%) and Minas Gerais (17.2%), Santa Catarina (13,7%) and Rio Grande do Sul (13,7%). Soccer and Volleyball were the sports most investigated by the research groups. Regarding theme, anxiety was the most published in the last five years by 10 groups, followed by motivation (9) and stress (7). There is lack of studies with sociological or historical analysis of Psychology of Sport and Exercise. We concluded that there was an increase in number of research groups of Psychology of Sport and Exercise in Brazil, especially in the last decade. However, the north and northeast regions still lack research groups in this area.